1984
DOI: 10.1002/j.1477-8696.1984.tb05478.x
|View full text |Cite
|
Sign up to set email alerts
|

The Double (Hale) Sunspot Cycle and Floods and Droughts in India

Abstract: H E quest for the possible relationships between sunspots and weatherlclimate T began even before Schwabe, a German astronomer, discovered the sunspot cycle in 1843. In spite of the controversy surrounding the claimed effects of sunspot cycles on weather and climate, consideration is being given to the possible implication for climatological forecasts. In recent years there has been a major revival of interest on the problems of the sun-weathedclimate relationships. New statistical methods and modem computers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…However, in the absence of an agreed mechanism to explain fluctuations in the weather in terms of variations in solar activity, the topic fell into disrepute; only in recent times has debate resumed and interest in possible sudweather relationships been renewed. Bhalme and Mooley (1981) and Bhalme and Jadhav (1984a) have found evidence for a c. 22 year cycle of floods and droughts in India, which they associate with the double (Hale) sunspot cycle. Similar findings were reported by Ananthakrishnan and Parthasarathy (1984).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, in the absence of an agreed mechanism to explain fluctuations in the weather in terms of variations in solar activity, the topic fell into disrepute; only in recent times has debate resumed and interest in possible sudweather relationships been renewed. Bhalme and Mooley (1981) and Bhalme and Jadhav (1984a) have found evidence for a c. 22 year cycle of floods and droughts in India, which they associate with the double (Hale) sunspot cycle. Similar findings were reported by Ananthakrishnan and Parthasarathy (1984).…”
Section: Introductionsupporting
confidence: 85%
“…AND PARTHASARATHY Ananthakrishnan and Parthasarathy (1984) have examined the annual rainfall figures (1871 to 1978) from 306 stations throughout India. As mentioned in the Introduction, these authors report a weak association between Indian rainfalls and the 22 year solar cycle-in good agreement with the earlier findings of Bhalme and Mooley (1981) and Bhalme and Jadhav (1984a). This association was more evident, however, in the initial 54 year period from 1871 to 1924 than in the subsequent period from 1925 to 1978.…”
Section: Rainfall In India: the Recent Studies Of Ananthakrishnanmentioning
confidence: 99%
“…For the same reason, India experienced a severe drought during 1899 but Indonesia did not. Bhalme and Jadhav (1984), while examining the association between large-scale flood occurrences over India and the double (Hale) sunspot cycle, have shown that large-scale floods have a tendency to cluster consistently in the positive (major) sunspot cycle. Variation in the annual mean sunspot number suggests that around 1996 it will enter a positive cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Walker (1933) was perhaps the first to study teleconnections between Indian monsoon rainfall and meteorological parameters at other parts of the earth. Later, several other studies investigated the links of Indian monsoon rainfall with different global climatic oscillations such as QuasiBiennial Oscillation (QBO) (Rao and Lakhole 1978;Vijayakumar and Kulkarni 1995;Claud and Pascal 2007), tidal forcing (Campbell et al 1983), El Nino Southern Oscillation (ENSO) (Shukla and Paolino 1983;Mooley and Parthasarathy 1983;Krishnakumar et al 1999;Gadgil et al 2004), Atlantic Multidecadal Oscillation (AMO) (Goswami et al 2006;Lu et al 2006;Zhang and Delworth 2006;Feng and Hu 2008); Equatorial Indian Ocean Oscillation (EQUINOO) (Gadgil et al 2004;Maity and Nagesh Kumar 2006a;Nagesh Kumar et al 2007), solar indices of sunspot cycle (SN), solar irradiance and sunspot area (Bhalme and Jadhav 1984;Krishnakumar et al 1999;Bhattcharya and Narasimha 2007;Azad 2011) etc. Such investigations helped in finding the potential inputs for rainfall forecasting models and many studies noted that the rainfall time series posses non-linear and non-stationary characteristics Raghukanth 2005, 2006;Maity and Nagesh Kumar 2006b; Nagesh Kumar et al 2007).…”
Section: Related Workmentioning
confidence: 99%